2004
DOI: 10.1081/drt-200025639
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination and Modeling of Sorption Isotherms ofErythrina Fusca LourBark

Abstract: The water sorption isotherms of the Erythrina fusca Lour bark at 30 and 40 C were determined over relative humidity ranging from 55 to 85%. The equilibrium moisture content was determined gravimetrically. The moisture sorption isotherms showed that the equilibrium moisture decreases with increase of temperature. Six models were used for to fit the experimental curves of equilibrium humidity. Parameters of each equation were determined by nonlinear regression analysis. The isosteric heat of moisture sorption wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…The desorption isotherm of black tea was studied by Panchriya et al [14] at the temperature range of 25 to 80 C and humidity range of 10 to 90% and found that GAB and Oswin equations showed good agreement with [15] reported that Oswin equation was able to describe the sorption isotherms of food products having S-shaped curves. Later, Ghodake et al [16] studied the sorption isotherms of withered leaves, black tea, and green tea at 20-40 C and showed that the best equation to fit their data was the Halsey model.…”
Section: Selection Of Suitable Sorption Isotherm Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…The desorption isotherm of black tea was studied by Panchriya et al [14] at the temperature range of 25 to 80 C and humidity range of 10 to 90% and found that GAB and Oswin equations showed good agreement with [15] reported that Oswin equation was able to describe the sorption isotherms of food products having S-shaped curves. Later, Ghodake et al [16] studied the sorption isotherms of withered leaves, black tea, and green tea at 20-40 C and showed that the best equation to fit their data was the Halsey model.…”
Section: Selection Of Suitable Sorption Isotherm Modelmentioning
confidence: 92%
“…Similar behavior was observed for other food products studied in the same range of moisture content. [15,19] Different mathematical equations were proposed to express the variation of net isosteric heat and differential entropy with moisture content. A Ratti model [20] was one of such mathematical relationship consisted of exponential and power functions.…”
Section: Isosteric Heat Of Sorption and Differential Entropymentioning
confidence: 99%
“…Each of these models has had some degree of success in reproducing equilibrium moisture content values depending on the water activity and the type of food material (Alvarez-Reyes et al, 2004;Arlabosse et al, 2003;Silva et al, 2006). Some of these models include BET, GAB, Henderson, Adam and Shove and Kuhn.…”
Section: Introductionmentioning
confidence: 97%
“…The differential heat of sorption h s can thus be determined by graphical differentiation of d(ln a w ) over d(1/T) as e,g, described by [12,1] . The graphical differentiation equals ∆ln(a w )/ ∆(1/T) which leads to [40] 21 ln…”
Section: Determining the Heat Of Sorption From Isothermsmentioning
confidence: 99%